2014
DOI: 10.1111/cei.12422
|View full text |Cite
|
Sign up to set email alerts
|

Are urinary levels of high mobility group box 1 markers of active nephritis in anti-neutrophil cytoplasmic antibody-associated vasculitis?

Abstract: SummaryThe objective of this study is to evaluate urinary high mobility group box 1 (HMGB1) levels as markers for active nephritis in patients with antineutrophil cytoplasmic antibody (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…In the present study, we demonstrated that the urinary levels of HMGB1 in active AAV patients were significantly higher than AAV patients in remission and healthy controls. Moreover, the level of HMGB1 in remission was lower than that in active phase for most patients with sequential urine samples, which was in line with the study by de Souza et al [ 22 ]. Further assessment revealed that the urinary HMGB1 level correlated with ESR, CRP and BVAS, which are commonly used parameters to evaluate the disease activity of AAV.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we demonstrated that the urinary levels of HMGB1 in active AAV patients were significantly higher than AAV patients in remission and healthy controls. Moreover, the level of HMGB1 in remission was lower than that in active phase for most patients with sequential urine samples, which was in line with the study by de Souza et al [ 22 ]. Further assessment revealed that the urinary HMGB1 level correlated with ESR, CRP and BVAS, which are commonly used parameters to evaluate the disease activity of AAV.…”
Section: Discussionsupporting
confidence: 91%
“…After binding to HMGB1, RAGE mediates multiple intracellular signaling pathways, including NF-κB, JAK/STAT, and MAPK families, and exerts a wide range of physiological and pathological effects [26]. HMGB1 levels have been shown to be higher in 27 children by KD than in healthy controls, as measured by Hoshina [27][28][29]. In order to be consistent with these studies, we collected serum samples from children in different phases of KD.…”
Section: Discussionmentioning
confidence: 87%
“…Recently, we observed circulating HMGB1 levels are associated with the disease activity of AAV [ 14 ], which was in line with and further extended the earlier related findings [ 38 - 40 ], although it remains controversial in studies by de Souza et al . [ 41 , 42 ]. Whether HMGB1 participated in the pathogenesis of AAV, and then the underlying mechanism was not fully clear yet.…”
Section: Discussionmentioning
confidence: 99%